2016
DOI: 10.1038/srep36209
|View full text |Cite
|
Sign up to set email alerts
|

Lycium barbarum polysaccharide attenuates high-fat diet-induced hepatic steatosis by up-regulating SIRT1 expression and deacetylase activity

Abstract: In this study, we aimed to investigate the protective effects and underlying mechanism of Lycium barbarum polysaccharide (LBP) on high-fat-induced nonalcoholic fatty liver disease (NAFLD). Recently, sirtuin 1 (SIRT1) has been shown to play an important role in the regulation of hepatocellular lipid metabolism. Here, we demonstrated that LBP up-regulates SIRT1 deacetylase activity and protein expression by enhancing the NAD+/NADH ratio. Subsequently, LBP promoted LKB1 deacetylation and AMPK phosphorylation via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 35 publications
5
51
0
Order By: Relevance
“…Our results showed that DM induced the downregulation of SIRT1 in the testes of diabetic rats and that LBP treatment increased the mRNA and protein expression levels of SIRT1 in the testes of diabetic rats. Our findings are in agreement with previous studies showing that LBP enhanced SIRT1 expression in hypoxic pulmonary vascular smooth muscle cells and in high-fat-dietinduced hepatic steatosis (35,36). The testis is a relatively hypoxic tissue, and HIF-1α regulates the primary transcriptional responses to hypoxic stress in normal and transformed cells, which plays an adaptive role in conferring protection against cell death in the testes (28).…”
Section: Discussionsupporting
confidence: 94%
“…Our results showed that DM induced the downregulation of SIRT1 in the testes of diabetic rats and that LBP treatment increased the mRNA and protein expression levels of SIRT1 in the testes of diabetic rats. Our findings are in agreement with previous studies showing that LBP enhanced SIRT1 expression in hypoxic pulmonary vascular smooth muscle cells and in high-fat-dietinduced hepatic steatosis (35,36). The testis is a relatively hypoxic tissue, and HIF-1α regulates the primary transcriptional responses to hypoxic stress in normal and transformed cells, which plays an adaptive role in conferring protection against cell death in the testes (28).…”
Section: Discussionsupporting
confidence: 94%
“…Some recent studies have shown that LBP enhances mitochondrial function by activating AMPKα2 32,33 and regulates lipid metabolism by upregulating SIRT1 expression and increasing deacetylase activity. 34 These studies on the function of LBP in the regulation of metabolism in nonmuscle tissues also indirectly suggest that LBP may be the active compound. Next, we will try to separate and purify the L. barbarum polysaccharide, narrow the range of effective components according to molecular weight and other indicators, and purify the uniform polysaccharide, and finally find the functional uniform polysaccharide or the combination of several uniform polysaccharides.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that LBP could enhance the proliferation of splenocytes in mice [34,35], activate macrophages [36], and promote both the phenotypic and functional maturation of DC [37]. Besides, LBP also has various other biological activities, such as neuroprotective effects [38,39], radioprotective activity [40], cardioprotective activity [41], and hepatoprotective effects [42,43]. Clinical trials have shown that LBP had remarkable protective effects in patients with type 2 diabetes [44].…”
Section: Discussionmentioning
confidence: 99%